New Immunofluorescence Assays for Detection of Human Herpesvirus 8-Specific Antibodies - Inoue, Naoki (American Society for Microbiology, 2000)
Several assays have been developed for detection of immunoglobulin G antibodies to Human herpesvirus 8 (HHV-8), including immunofluorescence assays (IFAs) and enzyme-linked immunosorbent assays (ELISAs). However, the specificity and sensitivity of these assays are not completely defined due to the lack of a “gold standard.” Although IFAs based on primary effusion lymphoma (PEL) cell lines are used widely, the assays can be confounded by nonspecific reactions against cellular components and potential cross-reaction with antibodies against other herpesviruses. To provide more reliable IFAs, we established recombinant Semliki Forest viruses (rSFVs) expressing the HHV-8-specific proteins ORF73 and K8.1 and used BHK-21 cells infected with these rSFVs for IFA (ORF73-IFA and K8.1-IFA). Expression of the HHV-8-specific proteins at very high levels by the rSFV system allowed easy scoring for IFA and thereby increased specificity. The rSFV system also allowed detection of antibodies against glycosylation-dependent epitopes of K8.1. Titers measured by rSFV-based IFAs and PEL-based IFAs correlated well (correlation coefficients of >0.9), and concordances of seroreactivities between rSFV-based and PEL-based IFAs were >97% (κ > 0.93). K8.1-IFA was more sensitive than either ORF73-IFA or peptide ELISAs. Using PEL-based lytic IFA as a reference assay, the sensitivity and specificity of K8.1-IFA were estimated to be 94 and 100%, respectively. HHV-8 prevalences determined by K8.1-IFA among the human immunodeficiency virus (HIV)-positive (HIV(+)) Kaposi's sarcoma (KS) patients, HIV(+) KS(−) patients, and healthy controls were 100, 65, and 6.7%, respectively, which were consistent with prior reports. Therefore, our rSFV-based IFAs may provide a specific and sensitive method for use in epidemiology studies. In addition, they will provide a basis for further development of diagnostic tests for HHV-8 infection.